Metabolic engineering of Clostridium carboxidivorans for enhanced ethanol and butanol production from syngas and glucose. (July 2019) - Cheng, Chi; Li, Weiming; Lin, Meng; Yang, Shang-Tian
Graphical abstract: Highlights: C. carboxidivorans was engineered to overexpress three genes for alcohol production. Overexpressing aor increased CO2 re-assimilation in heterotrophic growth on glucose. Strain overexpressing adhE2 produced ∼50% more ethanol from syngas. Strain overexpressing adhE2 and fnr produced 18% more butanol and 22% more ethanol. Abstract: Clostridium carboxidivorans can convert CO2, CO and H2 to ethanol and n -butanol; however, its industrial application is limited by the lack of tools for metabolic pathway engineering. In this study, C. carboxidivorans was successfully engineered to overexpress aor, adhE2, and fnr together with adhE2 or aor . In glucose fermentation, all engineered strains showed higher alcohol yields compared to the wild-type. Strains overexpressing aor showed CO2 re-assimilation during heterotrophic growth. In syngas fermentation, compared to the wild-type, the strain overexpressing adhE2 produced ∼50% more ethanol and the strain overexpressing adhE2 and fnr produced ∼18% more butanol and ∼22% more ethanol. Interestingly, both strains showed obvious acid re-assimilation, with <0.15 g/L total acid remaining at the end of fermentation. Overexpressing fnr with adhE2 enhanced butanol production compared to only adhE2 . This is the first report of overexpressing homologous and heterologous genes in C. carboxidivorans for enhancing alcohols production from syngas and glucose.